Determinants of urban labour earnings in Tanzania, 2000/01-06 - Vincent Leyaro; Priscilla Twumasi Baffour; Oliver Morrissey; Trudy Owens (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2014)
This paper presents analysis of urban areas in the Tanzania Integrated Labour Force Survey (ILFS) for 2000/01 and 2006 and the Urban Household Worker Survey (UHWS) for 2004, 2005 and 2006. The main aims are to estimate returns to education and to identify, conditioned on education and labour market experience, earnings differentials by gender and across sectors (public, private and informal). We confirm the general pattern that returns to education are increasing in level and years of education but note differences across sector of employment and the earnings distribution. Public sector workers (who tend to be more educated with longer tenure) and the self-employed with employees (small and micro enterprises) have the highest earnings whereas informal sector (self-employed without employees) and private sector wage earners have similar earnings on average (except for wage earners in large firms who have considerably higher earnings). Post-primary education is important in determining selection into wage employment, especially for the public sector. Allowing for selection, education has no additional effect on public sector wages, returns to education are concave for the self-employed but non-concave for the private wage sector. Quantile regressions reveal differential returns to education across the earnings distribution: primary and secondary education are inequality-reducing (more beneficial to those on lower earnings) whereas tertiary education is inequality-increasing.
Keywords: J6; J62; J69; 330; Labour Earnings; Returns to Education; Urban Labour; Tanzania